(untitled) (The Geographic Base, 2024)
This study focuses on the shifting livelihood strategies of the Raji community in Panchapuri Municipality, Surkhet, Nepal. The study employs quantitative as well as qualitative methods. Quantitative data were collected through census-based interviews with all 49 Raji household heads in the municipality. Similarly, qualitative information was also gathered through interviews with four key informants. The findings show that traditionally, a hunter-gathering and forest-dwelling indigenous group, the Raji community, has undergone significant changes in their way of life because of development interventions and the modernization process. They are experiencing increasing acculturation and assimilation into the mainstream culture of other caste people. Thus, the Raji community now commonly celebrates the mainstream Hindu festivals (Dashain, Tihar, Holi, Chaite Dashain, and Maghe Sankranti), reflecting broader cultural integration. Economically, many Raji people are now engaged in agriculture and other alternative forms of employment instead of their traditional occupation in fishing and boating. Economic necessity and limited opportunities are major causes of these changes to sustain their indigenous practices. Notably, the skill level in traditional fishing-based occupations is found to be declining, reflecting both generational shift and decreased dependence on these practices.